2013
DOI: 10.1007/s10344-013-0738-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of habitat management in the recovery of low-density populations of wild rabbit

Abstract: Understanding the relationship between spatial patterns of landscape attributes and population presence and abundance is essential for understanding population processes as well as supporting management and conservation strategies. This study evaluates the influence of three factors: environment, habitat management, and season on the presence and abundance of the wild rabbit (Oryctolagus cuniculus), an important prey species for Mediterranean endangered predator species. To address this issue, we estimated wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 54 publications
0
16
1
Order By: Relevance
“…Nevertheless, it demonstrates the important role of landscape heterogeneity, fragmentation and complexity in generalist species (Kenward 1982;Penteriani et al 2002;Campioni et al 2013). It is important to mention that the known relationship between increased proportion of ecotones (reflected in greater edge density) and greater rabbit abundance (Moreno and Villafuerte 1995;Delibes-Mateos et al 2010;Godinho et al 2013) could have, in part, masked the effect of the rabbit-related variables so that these had lower relative importance in our analysis. We also found that older individuals required smaller home ranges and covered smaller areas per night, which is probably the result of greater experience related to greater hunting efficiency (Marchetti and Price 1989;Wunderle 1991;Penteriani et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it demonstrates the important role of landscape heterogeneity, fragmentation and complexity in generalist species (Kenward 1982;Penteriani et al 2002;Campioni et al 2013). It is important to mention that the known relationship between increased proportion of ecotones (reflected in greater edge density) and greater rabbit abundance (Moreno and Villafuerte 1995;Delibes-Mateos et al 2010;Godinho et al 2013) could have, in part, masked the effect of the rabbit-related variables so that these had lower relative importance in our analysis. We also found that older individuals required smaller home ranges and covered smaller areas per night, which is probably the result of greater experience related to greater hunting efficiency (Marchetti and Price 1989;Wunderle 1991;Penteriani et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These results contrast with the ones obtained previously, because analyzed rabbit restockings were unsuccessful (Calvete et al , Moreno et al ). Habitat factors may have a strong influence on restocking (Godinho et al ) and warren occupation (Fernández‐Olalla et al ). However, there might be other factors influencing these dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The wild rabbit (Oryctolagus cuniculus), a key prey in the Iberian Peninsula (Delibes-Mateos, Redpath, Angulo, Ferreras, & Villafuerte, 2007) entering the diet of more than 40 predator species (Delibes-Mateos, Delibes, Ferreras, & Villafuerte, 2008;Delibes & Hiraldo, 1981), is one of the most notorious examples. The edge between natural or cultivated herbaceous and broken rock pieces covered with bush favours wild rabbit habitat quality (Godinho, Mestre, Ferreira, Machado, & Santos, 2013). The high abundance of this species attracts threatened predators to the area such as the booted eagle (Aquila pennata).…”
Section: Discussionmentioning
confidence: 99%